Precision Anesthetic Management of the Triple-Pathology Parturient: Graded Epidural Technique for Emergency Cesarean Section in Severe Tricuspid Regurgitation, Pulmonary Hypertension, and Systemic Neurofibromatosis - Purwoko; Fitri Hapsari Dewi; Helmi Ananta (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Maternal cardiac disease, specifically right-sided valvular lesions exacerbated by pulmonary hypertension, remains a primary driver of maternal mortality. The physiological demands of pregnancy act as a cardiovascular stress test, often leading to decompensation in patients with underlying pathology. This case describes the management of a triple-pathology parturient. Case presentation: A 37-year-old female (G2P1A0) at 34 weeks’ gestation presented with NYHA Class IV symptoms, including progressive dyspnea and orthopnea. Echocardiography revealed severe tricuspid regurgitation (regurgitant volume 112 mL), right ventricular dilatation, and a high probability of pulmonary hypertension with a mean pulmonary arterial pressure of 50.39 mmHg and a systolic pulmonary arterial pressure of 79.32 mmHg. Systemic neurofibromatosis added concerns regarding neuraxial anatomy and airway management. An emergency Cesarean Section was performed under a graded epidural technique using 0.375 percent Levobupivacaine and 50 mcg Fentanyl, administered in 3 mL increments every 5 minutes. Hemodynamic stability was maintained through strict fluid restriction of 300 mL and titrated vasopressors. Conclusion: A carefully titrated graded epidural provides superior stability in the hostile hemodynamics of right heart failure by allowing a slow, compensatory sympathetic blockade. Early multidisciplinary coordination is essential for success in complex cardio-obstetric cases.